North American Migration: Returns to Skill, Border Effects, and Mobility Costs - Hunt, Gary L.; Mueller, Richard E. (The Review of Economics and Statistics, 2004)
Utilizing a utility-maximizing, Roy-type, discrete choice model of worker location in Canadian provinces and U.S. states that incorporates returns to skill, amenities, fixed costs, distance, language, and border effects, we find that individuals with higher skills migrate to areas with higher returns and that the 49th parallel attenuates migration. Simulations indicate that equalizing returns in the two countries has a modest effect on cross-country migration; however, reductions in border effects tend to have large nonlinear effects on it. Our results confirm the qualitative results of previous research emphasizing the importance of returns to skill and border effects in migration decisions.